Pengaruh Budaya Organisasi, Komunikasi Organisasi, Lingkungan dan Kepuasan Kerja Terhadap Kinerja Pegawai di Kelurahan Jatimulya (Studi Kasus Kelurahan Jatimulya di Kabupaten Bekasi Jawa Barat) - Alfian Saputra; Milda Handayani; Rini Wijayaningsih (Universitas 45 Surabaya, 2025)
The Influence of Organizational Culture, Organizational Communication, Environment, and Job Satisfaction on Employee Performance in Jatimulya Urban Village This study aims to analyze the influence of organizational culture, organizational communication, work environment, and job satisfaction on employee performance in Jatimulya Urban Village. A quantitative method with multiple linear regression analysis was employed. The sample consisted of 40 employees selected using a saturated sampling method. Data were collected through questionnaires and analyzed using statistical software. The findings reveal that each independent variable has a positive and significant influence on employee performance. Collectively, the four variables contribute significantly to improving performance.